A Rapid and Simple Method for Determination of Uranium in Gattar Area by ICP-OES (Journal of Nuclear Technology in Applied Science, 2021)
This experiment was carried out to determine Uranium in a geological samples collected from Gattar area, North Eastern Desert of Egypt which examined by scanning electron microscope (EDX) to be characterized by hematization, silicification, muscovitization and fluoritization which are the most dominant alteration associated with the uranium mineralization. Inductively coupled plasma optical emission spectrometry (ICP-OES) was used for this study. Two methods of digestion of samples were used in the experiment and four emission lines were selected for uranium to choose the more sensitive one. The physical parameter conditions were adjusted by using standard solution of uranium to be 1200 W for RF power current, 35 psi for nebulizer gas pressure and 18 L/min for coolant gas pressure. The interference effect of some elements was studied on the selected line and showed that, the determination of uranium by ICP-OES is affected seriously by iron, aluminum, calcium, thorium and rare earth elements. The results of uranium determination at 303.199 nm with precipitation method were compared with the results from XRF method which shown acceptable accuracy and low time consuming other method.
Keywords: ICP-OES; Uranium; geological sample; granite; determination